Working with discursive genres in reading, writing and orality in a decolonial perspective of teaching in a public school in Ananindeua - da Silva Costa Aviz, Larissa; Rodrigues, Isabel Cristina França dos Santos (The ESPecialist, 2024)
It aims to show the practices of the project: “Reading Circuit: Reading to Be Happy”, UFPA. To achieve this, we mobilized the studies of Bakhtin (2016), Rojo (2012), Walsh (2013) and Freire (2021). The diversity of Amazonian knowledge supports the discussions. The research is collaborative qualitative articulated with the project mediators. The investigation took place in the 7th year class – public school, Ananindeua (Pa). The activities involved narratives, advertisements and regional interviews. The results pointed out the necessary articulations of reading, writing and speaking when working with discursive genres, enhancing and valuing the interaction between students and the knowledge that crosses the Amazon in Pará.